Модифіковані карбонові нановолокна як перспективний матеріал для суперконденсаторів - Кот Наталія Сергіївна (My University, 2023)
У роботі було досліджено вплив вторування на імпедансні властивості вуглецевих наноструктурованих волокон та порівняно отримані дані під впливом різних температур. Досліджено, що збільшення температури фторування карбонового нановолокна приводить до зменшення опору до-сліджуваних зразків та збільшення ємності. З графіків залежності імпеда-нсу температури від вторування встановлено можливість віднайти покра-щені умови виготовлення матеріалу для суперконденсаторів. Знайдено, що пояснення моделі залежності імпедансу від температури модифікації дозволить підібрати оптимальні умови виготовлення імпедансного мате-ріалу для суперконденсаторів. Ключові слова: модифіковані карбонові нановолокна, суперконден-сатор, метод імпедансної спектроскопії

The work investigates the influence of fluorination on the impedance properties of carbon nanofiber nanostructures and compares the obtained data under different temperatures. It has been found that increasing the temperature of carbon nanofiber fluorination leads to a decrease in the resistance of the investigated samples and an increase in capacitance. From the impedance-temperature dependence graphs, it was established that it is possible to find improved manufacturing conditions for supercapacitor materials. It has been found that constructing a model to explain the dependence of impedance on temperature modification will allow the selection of optimal conditions for the production of impedance materials for supercapacitors. The graduation thesis consists of 44 pages, includes 23 illustrations and 2 tables. The list of references includes 20 works. Keywords: modified carbon nanofibers, supercapacitor, impedance spectroscopy method.
Modified carbon nanofibers as a promising material for supercapacitors